Budidaya Cacing Tanah Sebagai Upaya Meminimalisir Potensi Polusi Tanah dan Pakan Ternak: (Implementasi Nilai-Nilai Ke-Islaman dan Lingkungan Hidup) - Zakiyah; Aziz, Abdul; Bakhri, Faisal; Paridayana, Yuli Nur; Syahrani, Zahra Aulia; Aisyi, Atika Rohadatul (Lembaga Penelitian, Penerbitan, dan Pengabdian Masyarakat, 2023)
Heavy metals are one of dozens of materials that cannot be decomposed in nature and can enter the environment through wastewater or other non-organic waste. Several methods are commonly used to remove heavy metals such as: reverse osmosis, chemical deposition, ion exchange, membrane processes, evaporation and solvent extraction, but most of these methods have disadvantages such as equipment and production costs which are also not cheap. Therefore, through this community service, KKN students and DPL invite the local community to map environmental problems, and together solve problems that the community can realize independently and sustainably, namely by cultivating earthworms. This solution is considered environmentally friendly, easy to implement, not high cost and can be an additional income for the local community. This Community Service uses a Participatory Action Research (PAR) approach. Which is oriented towards community empowerment. It is the community that has the main role in realizing the problem of potential soil contamination, and the additional supply of snakehead fish feed. The results of this community service stated that some residents, especially snakehead fish breeders, were happy because they were supported by other additional food for their snakehead fish cultivation. Meanwhile, soils that have the potential to be exposed to heavy metals can simply be treated naturally, inexpensively and are environmentally